The Maine Wabanaki-State Child Welfare Truth and Reconciliation Commission: Perceptions and Understandings - Collins, Bennett; McEvoy-Levy, Siobhan; Watson, Alison (Columbia University, 2014)
As this chapter demonstrates, the MWTRC represents a unique and creative approach to healing in communities affected by historical trauma. This chapter presents the history and context of the MWTRC. Drawing on interviews with the key participants4 in the MWTRC creation process, we explain the structure, mandate and role of the MWTRC and the accompanying community support structures that have been created. Key themes emerging from the interviews with the participants in the process are then discussed. The chapter shows that, originating in a deep understanding of the complex individual, family and community trauma that Wabanaki people have endured, the MWTRC embodies a collective desire for truth, healing and change. It provides a space for the articulation of a silenced history, and a process within which traumatic experiences and the trauma of memory can be shared in solidarity. The uniqueness of the MWTRC—a grassroots, community-organized, Indigenous community-state collaboration— makes it an important process for scholars and practitioners to follow. Although it faces challenges and tensions and involves difficult dialogues on race, privilege and accountability, this MWTRC is a new kind of truth commission, linking reconciliation with decolonization, and truth with practical policy change, in the process creating an important model of community-based conflict transformation and trauma recovery that has potentially wider implications for other communities—Indigenous, and non-Indigenous—seeking to reconcile, and to heal, after a period of long-term trauma. To see why such healing is truly necessary, this chapter turns to a summary of the historical context of trauma that the MWTRC aims to address.